The Oxford handbook of ethics and economics - White, Mark D., 1971- (Oxford : Oxford University Press, 2019)
The Oxford Handbook of Ethics and Economics provides a thorough survey of the various ways ethics can, does, and should inform economic theory and practice. The first part of the book, Foundations, explores how the most prominent schools of moral philosophy relate to economics; asks how morals relevant to economic behavior may have evolved; and explains how various approaches to economics incorporate ethics into their work. The second part, Applications, looks at the ethics of commerce, finance, and markets; uncovers the moral dilemmas involved with making decisions regarding social welfare, risk, and harm to others; and explores how ethics is relevant to major topics within economics, such as health care and the environment.
Adam Smith and the Study of Ethics in a Commercial Society / Stefanie Haeffele, Virgil Henry Storr -- Human Ethicality: Evidence and Insights from Behavioral Economics / Sanjit Dhami, Ali al-Nowaihi -- Ethics and Economics: A Complex Systems Approach / John B. Davis -- Evolution and Moral Motivation in Economics / Geoffrey M. Hodgson -- Economics and Ethics within the Austrian School of Economics / Peter Boettke, Kaitlyn Woltz -- Feminist Economics and Ethics / Ulrike Knobloch -- Economy and Culture: The Importance of Sense-Making / Arjo Klamer -- Humane Markets: The Classical Tradition of Political Economy / James R. Otteson -- Capitalism and Democracy: Allies, Rivals, or Strangers? / Julian Reiss -- Virtue and Economics, Horse and Cart / Jennifer A. Baker -- The Moral Status of Profit / Joseph Heath -- The Ethics of Making Risky Decisions for Others / Luc Bovens -- Ethics And, In, and For Labor Markets / Michael S. McPherson, Debra Satz -- Economics, Ethics, and Health Insurance / Daniel M. Hausman -- Deontological Morality and Economic Analysis of Law / Eyal Zamir, Barak Medina -- The Ethics and Economics of Ecological Justice / David Schmidtz -- Civil Rights, Employment, and Race / Brendan O'Flaherty -- The Tragedy of Economics: On the Nature of Economic Harm and the Responsibilities of Economists / George F. DeMartino -- Cost-Benefit Analysis and Social Welfare Functions / Matthew D. Adler -- Lessons from Economics / John Broome -- The Ethics of Money and Finance / Joakim Sandberg -- The Normative Economics of Social Risk / Marc Fleurbaey -- Economic Ethics and the Capability Approach / Constanze Binder, Ingrid Robeyns -- With All Due Respect: A Kantian Approach to Economics / Mark D. White -- Ethical Pluralism in Economics / Jonathan B. Wight -- Morality as a Complex Adaptive System: Rethinking Hayek's Social Ethics / Gerald Gaus -- On the Evolution of Ethics, Rationality, and Economic Behavior / David C. Rose.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 10, 2019).
Keywords: Economics -- Moral and ethical aspects; Economics; Economics